2005
DOI: 10.1016/j.orthres.2005.02.006
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of soft tissue coverage in the determination of bone kinematics using skin markers

Abstract: Accurate measurement of underlying bone positions is important for the understanding of normal movement and function, as well as for addressing clinical musculoskeletal or post-injury problems. Non-invasive measurement techniques are limited by the analysis technique and movement of peripheral soft tissues that can introduce significant measurement errors in reproducing the kinematics of the underlying bones when using external skin markers. Reflective markers, skeletally mounted to the right hind limb of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
154
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 151 publications
(159 citation statements)
references
References 23 publications
5
154
0
Order By: Relevance
“…To ensure that the segment motions were appropriately tracked, the relative position of the functional joint centers and axes to the segment marker clusters were transferred from the reference motions to each of the four activities. This was achieved by fitting the weighted optimum common shape marker clusters 23,37,38 from the reference motions to the raw marker clusters of the specific activity for each segment, and transforming the functional joint axes and centers with them. This method thus provided reliable joint centers and axes for activities with insufficient range of motion to functionally determine these parameters.…”
Section: Determination Of Lower Limb Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure that the segment motions were appropriately tracked, the relative position of the functional joint centers and axes to the segment marker clusters were transferred from the reference motions to each of the four activities. This was achieved by fitting the weighted optimum common shape marker clusters 23,37,38 from the reference motions to the raw marker clusters of the specific activity for each segment, and transforming the functional joint axes and centers with them. This method thus provided reliable joint centers and axes for activities with insufficient range of motion to functionally determine these parameters.…”
Section: Determination Of Lower Limb Motionmentioning
confidence: 99%
“…23,[35][36][37]60 The artifact associated with skin marker type and placement plays an important role in the accuracy of assessing skeletal kinematics, even when using functional methods, and such approaches should be applied carefully. 61 Here, unlike a previous study to determine the knee loading conditions, 31 the approach for determining kinematics combined robust functional methods 23,[35][36][37][38]60,62 with a global optimization approach 63,64 to also consider anatomical constraints such as invariant bone lengths, but also the 6 DoF relative transformations between the femoral and tibial segments for the specific TKR design. 39 TF forces predicted in previous studies that used similar musculoskeletal analyses to determine the knee loads, 31 but that could not employ these more sophisticated techniques to identify kinematics, agreed well with the in vivo forces reported here during walking.…”
mentioning
confidence: 99%
“…The accurate measurement of segment kinematics is challenging due to the complexity of the soft tissues moving relative to the underlying skeletal structures (Taylor et al 2005;Zemp et al 2014). As a result, motion capture varies from techniques using data extracted from simple videos, through retro-reflective markers attached to the subject's skin, to extensive measurement using e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to their increasing availability, non-invasive, high-speed and accurate nature, optoelectronic infra-red measurement devices have now become a standard technique for the capture of human movement. In order to improve the robustness of MS simulations (De Groote et al 2010;Lu et al 1997), specific approaches for the reduction of soft tissue artefact (Taylor et al 2005) and the assessment of the underlying robustness of MS simulation in OpenSim using different scaling methods and differently weighted kinematic concepts, as well as to estimate the resulting errors in terms of kinematics and kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…More commonly, the hip center is determined using a functional technique, whereby the center of rotation is estimated from motion capture data of the femur moving relative to the pelvis [10][11][12][13]. These techniques typically use reflective markers mounted on the skin and are prone to soft tissue artifacts which reduce the accuracy of measurement and are challenging to overcome [14,15]. Studies using mechanical linkages, in which the center of rotation is known a priori, have shown that circumduction motions give the most accurate estimate of the joint center [16] especially if the range of motion is at least 30° [16,17].…”
Section: Introductionmentioning
confidence: 99%